Security of ADS−B: State of the Art and Beyond - Strohmeier, M; Lenders, V; Martinovic, I (DCS, 2013)
Automatic dependent surveillance-broadcast (ADS-B) is the communications protocol currently being rolled out as part of next generation air transportation systems. As the heart of modern air traffic control, it will play an essential role in the protection of two billion passengers per year, besides being crucial to many other interest groups connected with aviation. The inherent lack of security measures in the ADS-B protocol has long been a topic in both the aviation and the academic community and is becoming ever more pressing with the quickly approaching mandatory implementation in most airspaces. This survey first analyzes the problems that have been reported about the ADS-B protocol in relation to its security. We then go on to survey the efforts that have been previously made concerning these problems, including possible countermeasures that have been proposed. Furthermore, the survey assesses additional security measures which have been developed more generally for related wireless networks such as sensor networks and vehicular ad hoc networks, including a taxonomy of all considered approaches.